The American revolutionaries a history in their own words, 1750-1800 - Meltzer, Milton 1915-. (New York Crowell, 1987)
Letters, diaries, memoirs, interviews, ballads, newspaper articles, and speeches depict life and events in the American colonies in the second half of the eighteenth century, with an emphasis on the years of the Revolutionary War.
Keywords: United States -- History -- Revolution, 1775-1783.; United States -- History -- French and Indian War, 1755-1763 -- Juvenile literature; United States -- History -- Confederation, 1783-1789 -- Juvenile literature; United States -- History -- Revolution, 1775-1783.; United States -- Social life and customs -- 1775-1783.